EDUCATIONAL ROBOTICS AS A TOOL OF KNOWLEDGE IN THE COURSE IN PHYSICS - D.K.Nasriddinov (Scholar Express Journal, 2023)
The article deals with the formation of modern engineering culture among students. Educational robotics is defined as one means of solving this problem. The components of robotics application technology in learning process in physics are revealed. The features of robotics as the means of knowledge are defined. The use of this means in research and technical creativity of students is discussed
Keywords: polytechnic principle; technical culture; learning physics; educational robotics